ANALISIS DAYA SAING USAHATANI TEBU DI PROPINSI JAWA TIMUR - MEWA ARIANI; ANDI ASKIN; JUNI HESTINA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
In the aspect of sugarcane farming system, increasing productivity and sucrose content ofsugar cane (rendemen) are exactly needed to increase the productivity of sugar and farmerincomes. The objective of the research is to analyze competitiveness of farmer’s sugarcanefarming system, which is measured by Policy Analysis Matrix (PAM). The research was held onsugar factories in East Java (Pesantren Baru in Kediri, Krebet Baru in Malang, Semboro inJember, and Pagotan in Madiun). The data are collected by interviewing farmers, 20 farmers ineach sugar factory. The results show that farmer’s sugarcane farming systems are financiallyprofitable with average advantage about 2.5-8 million per hectare. Farmer’s advantage in Madiunand Kediri districts are lower than it is in Malang and Jember districts. Although financiallysugarcane farming system is profitable, economically it is contrary. Farmer’s financial loss infrom 2.0 to 4.0 million per hectare. Sugarcane farming system in Madiun dan Kediri districts arenot having comparative advantage (DRCR<1), different from they are in Malang, Jemberdistricts. Sugarcane farming system in Madiun and Kediri districts will have comparativeadvantage if the productivity is increased by 20 percent or the international sugar price isincreased to 220 US/ton.